2011
DOI: 10.1007/s10584-011-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane effects on subtropical pine rocklands of the Florida Keys

Abstract: We investigate the effects of Hurricane Wilma's storm surge (23-24 October 2005) on the dominant tree Pinus elliottii var densa (South Florida slash pine) and rare plant species in subtropical pine rocklands of the Lower Florida Keys. We examine the role of elevation on species abundance in 1995 (Hurricane Betsy in 1965 (Hurricane Georges in 1998 (Hurricane Wilma in 2005 to investigate if hurricanes influence abundance by eliminating plants at lower elevation on Big Pine Key, the largest island in the Lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition to creating waterlogged and anoxic soils, hurricanes will increase electrolyte concentrations and osmotic potential of the soil solution and create a stressful, high salinity environment for both native and invasive plants [2][5]. Phenotypic plasticity, the potential of specific traits of a genotype to be expressed differently in distinct environments, is one of the mechanisms by which invasive plants can tolerate wide environmental variation and obtain an advantage in changing environments [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to creating waterlogged and anoxic soils, hurricanes will increase electrolyte concentrations and osmotic potential of the soil solution and create a stressful, high salinity environment for both native and invasive plants [2][5]. Phenotypic plasticity, the potential of specific traits of a genotype to be expressed differently in distinct environments, is one of the mechanisms by which invasive plants can tolerate wide environmental variation and obtain an advantage in changing environments [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that key deer prefer upland habitats including pine rocklands and upland hammocks [7], so we used a LiDar-derived digital elevation model to examine these habitat associations at a high resolution. We calculated the mean elevation within a 25 m buffer centered on the cameras because elevation is the driver of habitat changes in the Keys, but also reflects the susceptibility of sites to flooding and saltwater incursion from storms and hurricanes [22]. We used a buffer-wide average because some sites were artificially elevated on old roads and berms.…”
Section: Methodsmentioning
confidence: 99%
“…The contact of these two formations occurs at BPK, which is the Miami Limestone, averaging 5.7 m in thickness, and overlies the Key Largo Limestone (Hanson, 1980). The Miami oolitic layer can prevent the mixing of freshwater and saltwater, which protects BPK groundwater from saltwater intrusion (Saha et al, 2011).…”
Section: Study Areamentioning
confidence: 99%